2010
DOI: 10.1002/cyto.a.20994
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic flow cytometry by immunolabeled nanorods

Abstract: Fluorescence-based flow cytometry measures multiple cellular characteristics, including levels of receptor expression, by assessing the fluorescence intensity from a population of cells whose cell surface receptors are bound by a fluorescently labeled antibody or ligand for that receptor. Functionalized noble metal nanoparticles provide a complementary method of receptor labeling based on plasmonics for population analysis by flow cytometry. The potential benefits of using plasmonic nanoparticles to label cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Following 20 minutes of incubation at 37 °C, the antibody-NP solution was removed, and cells were washed with media twice before imaging [13,14]. The same protocol was previously tested and validated by confirming anti-EGFR specific binding of nanoparticles to EGFR positive cancer cells with appropriate control experiments [3, 1319]. Mie theory simulations indicate a substantially larger absorption cross section for 60 nm gold nanospheres as compared to lower diameter nanospheres, all of which have an absorption peak near 532 nm, the wavelength of the heating beam.…”
Section: Resultsmentioning
confidence: 99%
“…Following 20 minutes of incubation at 37 °C, the antibody-NP solution was removed, and cells were washed with media twice before imaging [13,14]. The same protocol was previously tested and validated by confirming anti-EGFR specific binding of nanoparticles to EGFR positive cancer cells with appropriate control experiments [3, 1319]. Mie theory simulations indicate a substantially larger absorption cross section for 60 nm gold nanospheres as compared to lower diameter nanospheres, all of which have an absorption peak near 532 nm, the wavelength of the heating beam.…”
Section: Resultsmentioning
confidence: 99%
“…For example, silver nanospheres can scatter light from 400–500 nm while gold nanospheres predominantly scatter light from 500–600 nm. This range is further extended by gold nanorods, which can be adjusted with peak resonant wavelengths anywhere between 600–2200 nm [14]. …”
Section: Theorymentioning
confidence: 99%
“…Simulations and experimental data have shown that there is a linear relationship between a GNR’s aspect ratio and its peak resonant wavelength [3, 24]. The longitudinal peak resonance can extend anywhere from 600 nm to 2200 nm [14]. This large range allows for the use of GNRs in many applications using both visible and NIR light.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Siiman et al noted that they were unsuccessful in creating side scatter clusters with nanoparticles smaller than 50 nm and speculated that other reports of side scatter cluster separation with 40‐nm gold particles may have been the result of accidental particle aggregation. More recently, Crow et al have reported the use of 30 nm rod‐shaped immunogold particles in a cellular assay (4). The method uses 20 min of vortex mixing.…”
mentioning
confidence: 99%